A General History of The Pyrates - Defoe, Daniel (Saga Egmont, 2022)
‘A General History of the Pyrates’ is a captivating account of some of history’s most notorious pirates. The author, writing as Captain Charles Johnson, blends fiction and non-fiction to provide readers with a most entertaining version of these iconic heroes and villains. This book was a massive success upon its first release due to its adventurous stories filled with danger and treasure and its influence lives on to this day as it shaped the modern view of pirates. Some of the best accounts in the book are of the infamous Blackbeard and the trailblazing female pirates Anne Bonny and Mary Read. ‘A General History of the Pyrates’ is the definitive story of the golden age of piracy and should be read by fans of books such as ‘Treasure Island’ and movies such as ‘Pirates of the Caribbean’.